Brain mapping of psychological processes with psychometric scales: An fMRI method for social neuroscience - Dimoka, Angelika (NeuroImage (Orlando, Fla.), 2011)
The functional neuroimaging literature has used many stimuli (e.g., games, pictures, sounds) in fMRI studies to induce activation in brain areas related to psychological processes. To improve the link among psychological processes and their brain mapping, this study integrates the theory of measurement in the social sciences with the functional neuroimaging literature to propose a simple method that localizes the neural correlates of psychological processes using psychometric scales as stimuli to induce brain activation. Two fMRI studies were performed to illustrate this method with 30 subjects who responded to psychometric scales for four psychological processes on 7-point Likert-type anchors while their brains were being scanned in an fMRI. The first study examined two psychological processes–trust and distrust–whose neural correlates are known. The second study examined two psychological processes specific to technology use context–perceived usefulness and perceived ease of use–whose neural correlates are still unknown. Results from the first fMRI study confirmed the neural correlates of trust in the caudate nucleus, putamen, anterior paracingulate cortex, and orbitofrontal cortex and of distrust in the amygdala and insular cortex, thus confirming the literature. The second fMRI study identified the neural correlates of perceived usefulness in the anterior cingulate cortex, caudate nucleus, and insular cortex and perceived ease of use in the dorsolateral prefrontal cortex, which are consistent with the technology use literature. The proposed brain mapping method with psychometric scales can inform the neurological nature of psychological processes, challenge existing measurement assumptions, and help advance brain mapping.